Intratumoral Fusobacterium nucleatum in Pancreatic Cancer: Current and Future Perspectives - Domenica Lucia D’Antonio; Anna Zenoniani; Samia Umme; Adriano Piattelli; Maria Cristina Curia (Pathogens)
The intratumoral microbiome plays a significant role in many cancers, such as lung, pancreatic, and colorectal cancer. Pancreatic cancer (PC) is one of the most lethal malignancies and is often diagnosed at advanced stages. Fusobacterium nucleatum (Fn), an anaerobic Gram-negative bacterium primarily residing in the oral cavity, has garnered significant attention for its emerging role in several extra-oral human diseases and, lately, in pancreatic cancer progression and prognosis. It is now recognized as oncobacterium. Fn engages in pancreatic tumorigenesis and metastasis through multifaceted mechanisms, including immune response modulation, virulence factors, control of cell proliferation, intestinal metabolite interactions, DNA damage, and epithelial–mesenchymal transition. Additionally, compelling research suggests that Fn may exert detrimental effects on cancer treatment outcomes. This paper extends the perspective to pancreatic cancer associated with Fn. The central focus is to unravel the oncogenomic changes driven by Fn in colonization, initiation, and promotion of pancreatic cancer development. The presence of Fusobacterium species can be considered a prognostic marker of PC, and it is also correlated to chemoresistance. Furthermore, this review underscores the clinical research significance of Fn as a potential tumor biomarker and therapeutic target, offering a novel outlook on its applicability in cancer detection and prognostic assessment. It is thought that given the role of Fn in tumor formation and metastasis processes via its FadA, FapA, Fap2, and RadD, new therapies for tumor treatment targeting Fn will be developed.